Contemporary possibilities of hearing improvement in various ages - Skarżyński, Henryk (Przewodnik Lekarza/Guide for GPs, 2010)
In the last years the team of the Institute of Physiology and Pathology of Hearing undertook numerous scientific, clinical didactic and organizational activities that allowed us to elaborate new diagnostic programs, new tools and equipment, new means of treatment and rehabilitation of hearing impairments. These actions were conditioned by numerous factors triggering off a significant breakthrough in this area of science and medicine. Considering the new advanced technologies, new equipment, new materials applied in reconstructive surgery, new middle and inner ear implant systems, brainstem implant systems, large surgical experience and significant social needs – it would be fully justified to call the present breakthrough the “New Era in Otology and Otosurgery”. In our everyday clinical practice it effected in improved quality and extended range of services offered to patients. Present opportunity to improve hearing in practically all ages of patients reflect tremendous progress and meet significant expectations of the informative society. The possibility to combine in one inner ear natural acoustic stimulation in case of normal hearing on low frequencies with properly set electric stimulation in the deaf part of the inner ear is the crowing scientific and clinical achievement.